A Study on Financial Soundness at Indonesian Islamic Bank - Hidayah, Islamiati; Hariyanti, Sri; Kusumawardhany, Sayekti Indah (Iqtishodia: Jurnal Ekonomi Syariah, 2024)
This study aims to investigate the soundness of Islamic Bank in Indonesia. Particularly at PT. Bank Muamalat Indonesia, Tbk through RGEC (Risk Profile, Good Corporate Governance, Earning, and Capital). This study is a quantiative study and employs multiple regression analysis to analyze the data from annual report of Bank Muamalat Indonesia. RGEC method was employes to measure the financial distress which includes components of Risk Profile, Good Corporate Governance, Earnings, and Capital. The Risk Profile is proxied by Non-Performing Finance (NPF) and Financing to Deposit Ratio (FDR). Earnings are proxied by Return on Assets (ROA), Return on Equity (ROE). Capital is peroxided by the Capital Adequacy Ratio (CAR). The result of this study shows NPF, FDR, RoA, RoE, and CAR are partially and simultanousely influence financial distress of Islamic Bank especially in Bank Muamalat Indonesia. Particularly, NPF and RoE have a positive relationship with financial distress while FDR, RoA, and CAR have a negative relationship with financial distress